(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2021)
Indonesia is one of the most impactful Islamic economies country in the world which has various potentials in the development of the Islamic economic sector, including banking. This study aims to measure and analyze the performance of Islamic State-owned banks in Indonesia before merging into Bank Syariah Indonesia (BSI). This research is descriptive quantitative research by measuring the financial performance of the bank through the level of profitability and risk ratios. The results of the study show that in general the performance of the 3 state-owned Islamic banks is good and experiencing growth, so it is assessed that by merging assets and markets, Islamic banks in Indonesia can grow faster.